Phylogenetic diversity of microorganisms associated with three marine sponges from Mien Trung sea of Vietnam - Cuc, Nguyen Thi Kim; Dat, Ton That Huu; Hong, Tran Thi; Cuong, Pham Viet (Vietnam Journal of Science and Technology, 2017)
Using culture - independent technique, hypervariable V4 region of 16S rDNA library sequencing by MiSEq, the baterial communities of three host sponges Rhabdastrella sp. DN, Spheciospongia sp. QT and Clathria sp. NT from Mien Trung sea were characterized. The phylogenetic analysis showed that bacterial community structures of the three investigated sponges similar to each other regarding 10 common phyla, although abundance of these phyla was different for each sponge. Phylum Thaumarchaeota was rich component for three sponges, especially in NT sponge (31.89%). In this sponge, 3 phyla Planctomycetes, Verrucomicrobia and Firmicutes were undetected in other 2 sponge samples. Phyla Cyanobacteria was observed only in DN sponge. The obtained amplicons were assigned in different taxonomic levels (class, order, family and genus) based on Silva database. At class level, Gammaproteobacteria was abundant in three sponges; and  Caldilineae, Marine-group I were dominant in DN; mealwile, in QT other dominant classes were Marine-group I and Betaproteobacteria. For NT, they were Cytophaga and Deferribacteres. In general, all three sponges harbored abundant and genetically diverse microbial associated consortia and they shared several common bacterial operational taxonomic units, although with different abundance.